The Role Of Modernization Factor On Public Awareness About Corruption In Iraq. The Mediating Effects Of Social Networking And Culture - Falih Hussein, Maytham; Jano, Zanariah; Hashim, Rahman (Opción, 2019)
The proposition of people’s awareness about corruption struggles potency at early stages, especially public officials accepting bribery in Iraq. Yet, transfer- ing awareness about corruption toward action is a deep further complicated and difficult burden and this was proved within the review about modern- ization factors and people’s awareness about corruption utilization litera- ture. The research goal of this study was to develop an integrated model of modernization factors and people’s awareness about corruption. By adopting Modernization Theory as the idea of characterized by changes of norms and values toward corruption dilemma and Cultural Theory as the logical impli- cations for a group of people to behave in corrupt ways and leading to the conclusion that fighting corruption entails cultural change. Through a survey conducted with 310 of students randomally selected from Bagadad University and analysed by SmartPlas, we find that the modernization factors of Cultur- al, Economic, Political and Judiciary have positive effect of public awareness about corruption. We also find that social network and culture play an effective mediatoring roles on the relationship between modernalition and people awareness about corruption